INTERFERENCE ON THE NOVEL â€œAROUND THE WORLD IN EIGHTY DAYSâ€ BY JULES VERNE - Yogi Yahya; Jenie Posumah; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2023)
This research discusses about Interferencing a novel called Around the Â world in Eighty Days by Jules Verne. The work tells the story of two travelers that grow to a trio and then a foursome as they fight their way through countless obstacles to reach home in time.Â The work focuses of a wealthy british bachelor, named Phileas Fogg, who spend his days gambling with friends at the social club and spent his night alone. Around the World in Eighty DaysÂ was published in 1873. The story follows two travelers that grow to a trio and then a foursome as they fight their way through countless obstacles to reach home. This research divided in three parts, first one is what should have we interference on this novel, the second is describing phileas foggâ€™s character, and the third is what makes the main character want to fulfill his dreams to be able to travel around the world.